Technical survival of CAPD catheters: comparison between percutaneous and conventional surgical placement techniques - (:unkn) unknown (OXFORD UNIV PRESS, 2001)
Background. Percutaneous peritoneal dialysis catheter (PDC) placement is a well-tolerated, rapidly performed bedside procedure that allows a rapid initiation of CAPD. We compared the technical survival of PDCs while comparing the mode of insertion. Methods. We retrospectively reviewed 215 PDCs inserted over a 60-month period in 191 patients on CAPD therapy. Of these, 133 were placed percutaneously by nephrology staff (group P) and 82 were placed using conventional surgical techniques by surgical staff (group S). The total experience accumulated was 4000 patient-months: 2260 patient-months in group P and 1740 patient-months in group S. Results. The incidence of complications in PDCs did not differ between the groups (1 episode/33 patient-months in group P and I episode/29 patient-months in group S). Two episodes of early leakage and 9 episodes of late leakage were observed in group P compared with one early leakage and 4 episodes of late leakage in group S. Of the mechanical complications in group P, 8.86% were due to catheter malfunction, including catheter tip migration and obstruction, compared with 12.63% in group S. The incidence of catheter infections was 1 episode/73 patient-months in group P and I episode/62 patient-months in group S. Significantly more catheters were removed in group S compared with group P (40% vs 16%, P <0.001). One-year and 2-year technical survivals were 90% and 82% in group P, and 73% and 60% in group S (P=0.0032), respectively. Conclusions. Percutaneous bedside placement of PDCs by nephrologists provides a safe and reliable access for peritoneal dialysis.
Keywords: CAPD; methods of insertion; peritoneal dialysis catheters; technical survival; PERITONEAL-DIALYSIS CATHETERS; 14-YEAR EXPERIENCE; STRAIGHT; CUFF; COMPLICATIONS; IMPLANTATION; ACCESS